1997
DOI: 10.1007/s004420050111
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and inter-specific variation in canopy photosynthesis in a mixed deciduous forest

Abstract: Within the same forest, photosynthesis can vary greatly among species and within an individual tree. Quantifying the magnitude of variation in leaf-level photosynthesis in a forest canopy will improve our understanding of and ability to model forest carbon cycling. This information requires extensive sampling of photosynthesis in the canopy. We used a 22-m-tall, four-wheel-drive aerial lift to reach five to ten leaves from the tops of numerous individuals of several species of temperate deciduous trees in cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
4
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 37 publications
11
65
4
1
Order By: Relevance
“…When the size of plant exceeds the boundary of an environmental factor the overall phenotypic integrity is disrupted and significant intraspecific variability occurs (Bassow and Bazzaz, 1997;Gutschick, 1999;Torres Boeger and Poulson, 2003). Despite the well established assumption that both P. perfoliatus and M. spicatum are shade-tolerant plants, our results show that only by the end of summer and only the basal part of these macrophytes were located at depth with minimal, i.e.…”
Section: Discussioncontrasting
confidence: 48%
“…When the size of plant exceeds the boundary of an environmental factor the overall phenotypic integrity is disrupted and significant intraspecific variability occurs (Bassow and Bazzaz, 1997;Gutschick, 1999;Torres Boeger and Poulson, 2003). Despite the well established assumption that both P. perfoliatus and M. spicatum are shade-tolerant plants, our results show that only by the end of summer and only the basal part of these macrophytes were located at depth with minimal, i.e.…”
Section: Discussioncontrasting
confidence: 48%
“…Leverenz (1996) reported that P max of sun leaves increased from shade tolerant Abies (approximately 7.0 µmol·m -2 ·s -1 ) to shade intolerant Pinus (approximately 16.0 µmol·m -2 ·s -1 ) species. Bassow and Bazzaz (1997) also found that P max decreased with increasing shade tolerance in temperate deciduous trees. Apparently the cost of maintaining high photosynthetic capacity is not justified in shade.…”
Section: Leaf-level Carbon Acquisitionmentioning
confidence: 75%
“…Diameter growth has been positively related to photosynthetic biomass and its efficiency [26,27,47], as well as to the relationships between crown ratio and stem taper [28,[49][50][51]. Shade intolerant tree species, such as jack pine [52], exhibit a more open crown and a high photosynthetic capacity [53] and the dominant trees of this species seems to benefit from the sunlight access during the first years after plantation establishment. A reduction of photosynthesis and carbon production is normally observed when intra-and inter-specific competition occurs (crown closure).…”
Section: Spacing and Tree Growthmentioning
confidence: 99%